Fundamentals of Professional Cooking and Baking - Gonzalez, Gene R.; Sandique, Jill F. (Pasig City, 2004)
A comprehensive guide designed for culinary students and professionals, covering fundamental techniques in cooking and baking, with practical applications in the food industry.
Keywords: Cookery, Asian; Baking; Food and industry trade